2011
DOI: 10.1163/187847511x588746
|View full text |Cite
|
Sign up to set email alerts
|

Colour Constancy as Measured by Least Dissimilar Matching

Abstract: Although asymmetric colour matching has been widely used in experiments on colour constancy, an exact colour match between objects lit by different chromatic lights is impossible to achieve. We used a modification of this technique, instructing our observers to establish the least dissimilar pair of differently illuminated coloured papers. The stimulus display consisted of two identical sets of 22 Munsell papers illuminated independently by neutral, yellow, blue, green and red lights. The lights produced appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 42 publications
4
44
0
4
Order By: Relevance
“…The illuminants are Logvinenko and Tokunaga's [20] red (R2) and neutral (N) as shown in Fig. 6 As another test of the proposed GM prediction method versus von Kries and Bradford, we used the 20 Munsell papers used in the asymmetric matching experiments of Logvinenko and Tokunaga [20] under their green and neutral ("white") illuminants. The spectra of both these illuminants are plotted in Fig.…”
Section: Color Signal Prediction Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The illuminants are Logvinenko and Tokunaga's [20] red (R2) and neutral (N) as shown in Fig. 6 As another test of the proposed GM prediction method versus von Kries and Bradford, we used the 20 Munsell papers used in the asymmetric matching experiments of Logvinenko and Tokunaga [20] under their green and neutral ("white") illuminants. The spectra of both these illuminants are plotted in Fig.…”
Section: Color Signal Prediction Resultsmentioning
confidence: 99%
“…As a final test of GM prediction in comparison to von Kries and Bradford prediction, we used all 30 nonidentical pairs of the six Logvinenko and Tokunaga's [20] illuminants shown in Fig. 6.…”
Section: Color Signal Prediction Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the reference illuminant D65, CIE1964 standard colorimetric observer (10 ), and SOCS data set, taking the first color sample in ColorChecker24 color data set as an example, we computed corresponding 53 486 metameric pairs as our metamerism data set M. There are 28 948 metamerism spectral reflectance curves, where the magnitude of each band that do not fall within the range of [0,1] will be deleted. The rest of color samples are deduced by the same, and a total of 24 metamerism data sets are derived.…”
Section: Metameric Spectra Data Setmentioning
confidence: 99%
“…Following the recent discovery of color constancy and metamerism mismatching phenomenon, Logvinenko et al argued that color constancy cannot be achieved for all reflecting objects. 10 Moreover, Berns et al suggested that the color differences calculated at constant chromatic adaptation by their proposed method will give greater utility than indices calculated by the normal approach. 11 Wang et al believed that the effect of L* on reflectance is much greater than the effect of saturation (a* or b*).…”
Section: Introductionmentioning
confidence: 99%